Meningkatkan Kompetensi Guru Memotivasi Siswa Melalui Running Dictation Strategi Pelajaran Bahasa Inggris - Yulita Suarni (Dinasti Research, 2023)
Learning at SMA Negeri 1 Painan, especially the problem found in language learning was that the teacher was still weak in motivating students during PBM. This is evidenced by the fact that there are still many students who do not focus when the teaching and learning process takes place. To overcome this problem the authors conducted school action research to improve teacher competence to find the right strategy in motivating student learning. This research is entitled to improve teacher competence in motivating student learning through running dictation strategies in language lessons at SMA 1 Lunang. The purpose of this study was to see how far there was an increase in students' learning motivation and students' enjoyment of learning a language. The action is carried out in two cycles. The data were obtained from observation sheets recorded by an observer who recorded student activities observed during the learning process. Based on the research results, the percentage of students increased from cycle I to cycle II, from 65.7% to 86%. Compared to the average percentage before the study it was only 54.4 as many as 11.6% of students. It can be concluded that learning by creating a fun learning atmosphere through running dictation strategies can increase student motivation.